2015
DOI: 10.1186/s13256-015-0569-9
|View full text |Cite
|
Sign up to set email alerts
|

Use of a porcine dermal collagen implant for contaminated abdominal wall reconstruction in a 105-year-old woman: a case report and review of the literature

Abstract: IntroductionRepair of contaminated abdominal wall defect in a geriatric patient is a challenge for the surgeon. We present the case of the oldest patient (105-years old) to successfully undergo a single-stage repair of a contaminated abdominal wall defect with a Permacol™ implant.Case presentationA 105-year-old Caucasian woman presented to our emergency room with a clinical and radiological diagnosis of small bowel obstruction due to prior operative adhesions. She underwent laparotomy with small bowel resectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…The medical evaluation for patients with advanced ages should focus on identifying risk factors, optimizing status, predicting complications, and providing appropriate information. Some studies have described cases of surgery in patients aged >100 years, for example, coronary bypass surgery in a 105-year-old patient 3) , abdominal wall reconstruction in a 105-year-old patient 4) , and osteosynthesis for hip fracture in a 107-year-old patient 5) . They reported that in each case, detailed risk assessment, surgical planning, and meticulous postoperative management were the reasons for the successful surgical treatment [3][4][5] .…”
Section: Discussionmentioning
confidence: 99%
“…The medical evaluation for patients with advanced ages should focus on identifying risk factors, optimizing status, predicting complications, and providing appropriate information. Some studies have described cases of surgery in patients aged >100 years, for example, coronary bypass surgery in a 105-year-old patient 3) , abdominal wall reconstruction in a 105-year-old patient 4) , and osteosynthesis for hip fracture in a 107-year-old patient 5) . They reported that in each case, detailed risk assessment, surgical planning, and meticulous postoperative management were the reasons for the successful surgical treatment [3][4][5] .…”
Section: Discussionmentioning
confidence: 99%